Dedication - APLA, Exectutive (Linguistica Atlantica, 2009)
On the occasion of his retirement, the Atlantic Provinces Linguistic Association lakes the opportunity to dedicate this issue of LINGUISTICA ATLANTICA to James Black - Professor, former Chair of the Linguistics Department and former Associate Dean of Arts at Memorial University, Newfoundland and Labrador, and past editor of this journal.